Press, politics, and the public sphere in Europe and North America, 1760-1820 - Barker, Hannah, 1967-; Burrows, Simon, 1966- (Cambridge University Press, 2002)
Newspapers are a vital component of print and political cultures, as they informed and documented social and political upheavals between 1750-1850. Despite the influence attributed to newspapers, little is known about the press itself. This collection aims to fill this gap by examining the press of Europe and America.